Applications and Expectations of Fuel Cells and Lithium Ion Batteries - (:unkn) unknown (Springer Science and Business Media Deutschland GmbH, 2022)
One substantial need for human beings is “energy” in daily life. To generate energy especially from fossil fuels are frequently utilized. However; they are about to deplete day by day and this fluctuates fuel prices in addition to their adverse effect on environment. Leading countries are shifting their energy resources from fossil fuels to renewables sources such as wind energy, solar energy, biomass energy. Among the renewable sources, hydrogen energy is one of the most candidates to mitigate greenhouse gas emission and climate change. One other issue is storage of these generated energy. Increase in the demand of renewable energy is a driving force to develop more Lithium ion batteries (LIBs) and new battery chemistries. In the article, the comparison of batteries and fuel cells in various aspects such as application areas and cost are given. The aim of this paper is to give comprehensive information about the better understanding of future of energy storage applications. According to literature, future of energy storage systems will be affected strongly by the developments in storage materials and systems. © 2022, The Author(s), under exclusive license to Springer Nature Switzerland AG.
Keywords: Battery; Electric vehicle; Electricity; Energy; Fuel cell; Fuel cell vehicle; Hydrogen; Lithium